Hydrogen Adsorption Properties of Nano- and Microstructures of ZnO. (27th October 2013) - Wahab, Rizwan; Khan, Farheen; Ahmad, Naushad; Shin, Hyung-Shik; Musarrat, Javed; Al-Khedhairy, Abdulaziz A.
Abstract : Nanoparticles, microflowers, and microspheres of zinc oxide have been synthesized in a large quantity via solution process at low temperature and were tested for the hydrogen adsorption studies. The experiments were carried out using Sievert's apparatus which resulted in highest hydrogen adsorption value for nanoparticles is 1.220 wt%, whereas for microflower composed with thin sheets value reduced ( 1.011 wt%) but in case of microspheres composed with nanoparticles having below one wt% ( 0.966 wt%). The FE-SEM and XRD clarify that the obtained products are crystalline with wurtzite phase. Including morphological and crystalline characterization, the surface area of the prepared nano- and microstructures was observed with BET.